(untitled) (Medico Legal Update, 2021)
Islamic boarding schools (Pesantren) are Islamic educational institutions in Indonesia. The Ministry of Health of the Republic of Indonesia has launched a concept to encourage people to care about their health, namely the Clean and Healthy Behavior (PHBS). Islamic boarding schools also have health problems so they need attention in efforts to improve public health. The health effort undertaken at the Pesantren is Poskestren (Pesantren Health Care). Based on the Health Department Data of East Java Provincial (2019), there are 3,965 islamic boarding schools with 1,284 Poskestren in East Java province. Poskestren can be a solution in solving health problems in Pesantren. Therefore the Poskestren must be arranged properly. In health promotion there are health promotion strategies which consist of advocacy, community development, community empowerment and partnerships. This health promotion strategy can be a reference in the implementation of the Poskestren in Pesantren.